2021
DOI: 10.56369/tsaes.3306
|View full text |Cite
|
Sign up to set email alerts
|

Estimación De Emisión De Metano Entérico en Sistemas De Producción De Leche Bovina en Pequeña Escala Bajo Diferentes Estrategias De Alimentación

Abstract: <p><strong>Background: </strong>Small-scale dairy systems are a development option, and in Mexico they represent over 78% of dairy farms providing 37% of milk production. They are a source of employment and income in rural areas that enable dairy families to overcome poverty. However, ruminant production systems emit 17% of world methane, a greenhouse gas that affects climate change. Strategies must be devised to reduce the environmental footprint of dairy systems through increase productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although protein content showed a negative correlation, it did not show as high a negative correlation as starch content. In the case of the grass species, the rapid fermentation of starch decreases the ruminal pH, favoring the formation of propionate, which contributes to reducing the availability of hydrogen for the formation of methane, following what was stated by Carrillo-Hernández et al (2021).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although protein content showed a negative correlation, it did not show as high a negative correlation as starch content. In the case of the grass species, the rapid fermentation of starch decreases the ruminal pH, favoring the formation of propionate, which contributes to reducing the availability of hydrogen for the formation of methane, following what was stated by Carrillo-Hernández et al (2021).…”
Section: Discussionmentioning
confidence: 67%
“…It is estimated that the livestock sector worldwide is responsible for 17% of methane (Carrillo-Hernández et al, 2021;Pámanes-Carrasco et al, 2020). Latin American countries are characterized by low production of meat and milk of animal origin.…”
Section: Introductionmentioning
confidence: 99%
“…There is scarce information on the nutritional value of silages from SGC mixtures. Carrillo Hernández et al (2023) reported for a mixture of BLY and RYE at the milk stage, with RYE dominance, and IVDMD of 538.9 g/kg 1 DM. Coblentz et al (2018) working with different TRT cultivars in monoculture reported digestibilities of 610 g/kg 1 DM at anthesis, and 606 g/kg 1 DM in milk stage.…”
Section: Chemical Composition Of Silagesmentioning
confidence: 99%
“…These are sown as monoculture or as binary crops, with benefits of the latter in terms of productivity an quality (Liesch et al, 2011). In that sense, silages from small-grain cereal forage mixtures have been demonstrated as an option to provide low cost forage for times of scarcity (Carrillo-Hernández et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The production systems that benefit from the use of these forages include small-scale dairy systems, which are considered a feasible instrument to stimulate economic growth and reduce poverty; additionally, they contribute 37% of the domestic milk production [8]. However, there are more systems that benefit from their use, such as sheep production systems.…”
Section: Introductionmentioning
confidence: 99%